SCO companion the essential guide for users and system administrators - Mohr, James (Prentice Hall PTR, 1996)
Former SCO support engineer James Mohr answers the most commonly asked questions and concerns of SCO users, and provides hard-to-find information about how SCO UNIX components work together, how they interact with PC hardware - and with users. Whether you're a user or a system administrator, SCO Companion will help you understand all the fundamentals of SCO UNIX - from its shells and basic utilities to advanced